Endoscopic ultrasound-guided, through-the-needle forceps biopsy for diagnosis of pancreatic cystic lesions: a systematic review - Guzmán-Calderón, Edson; Martinez-Moreno, Belen; Casellas, Juan A.; de Madaria, Enrique; Aparicio, José Ramón (Endoscopy International Open, 2020)
Background and study aims Pancreatic cystic lesions (PCL), are a heterogeneous group of cystic lesions. Some patients with PCLs have a significantly higher overall risk of pancreatic cancer and the only test that can differentiate benign and malignnat PCL is fine-needle aspiration plus cytological analysis, but its sensitivity is very low. Through-the-needle direct intracystic biopsy is a technique that allows acquisition of targeted tissue from PCLs and it may improve the diagnostic yield for them. The aim of this study was to review articles about endoscopic ultrasound (EUS)-guided through-the-needle intracystic biopsy for targeted tissue acquisition and diagnosis of PCLs.Methods A systematic review of computerized bibliographic databases was carried out for studies of EUS-guided through-the-needle forceps biopsy (EUS-TTNB) of PCLs. The percentages and their 95 % confidence intervals (CIs) were calculated for all the considered endpoints (technical success, adequate specimens, adverse events (AEs), and overall diagnosis).Results Overall, eight studies with a total of 423 patients were identified. Pooled technical success was 95.6 % of the cases (399/423), (95 % CI, 93.2 %–97.3 %). Technical failure rate was 5.1 % (24 cases). Frequency of adequate specimens was 82.2 %, (95 % CI, 78.5 %–85.8 %). Adverse events were reported in seven of the eight studies. Forty-two total adverse events were reported (10.1 %) (95 % CI, 7.3 %–13.6 %). The overall ability to provide a specific diagnosis with EUS-TTNB for diagnosis of pancreatic cystic lesions was 74.6 % (313 cases), (95 % CI: 70.2 %–78.7 %). The most frequent diagnoses found with EUS-TTNB were mucinous cystic neoplasms (MCN) in 96 cases (30.6 %), IPMN in 80 cases (25.5 %), and serous cystoadenoma neoplasm (SCN) in 48 cases (15.3 %).Conclusions Through-the-needle forceps biopsy appears to be effective and safe, with few AE for diagnosis of pancreatic cystic lesions. This technique had acceptable rates of technical and clinical success and an excellent safety profile. TTNB is associated with a high tissue acquisition yield and provided additional diagnostic yield for mucinous pancreatic lesions. TTNB may be a useful adjunctive tool for EUS-guided assessment of PCLs.